Mamu: trans indigenous and two-spirit youth coming together to define their needs and to take action - Pullen Sansfacon, Annie; Boivin, Johnny; Partridge, Pasha A.; Labelle, Diane; Lee, Edward Ou Jin (International Journal of LGBTQ+ Youth Studies, 2025)
Youth who are both trans and Indigenous, whether or not they identify as Two-Spirit experience multiple forms of structural violence at the intersection of gender and Indigeneity. Whether these young people live on or off reserve, the studies have highlighted specific challenges experienced in particular in connection with self-identification, conditions of significant poverty, violence, and lack of access to health care. health. This paper presents the results of an action research project using Talking Circles co-facilitated by an Elder and two Two-Spirit young people. Developed in collaboration with a local community organization the Talking Circles took place over a period of 21 meetings held between September 2021 and April 2022, in Tiohtià:ke (Montreal) and online. The participants of the Talking Circles discussed their most pressing issues, the underlying causes of these issues, and possible solutions to address them. This paper examines the themes uncovered during the projects as well as three main issues that emerged from the discussions: the lack of access to safe spaces, the lack of representation and the lack of education. The article also discusses their resilience and how they take action to change the world around them.